Money, Income, Prices, and Interest Rates - Friedman, Benjamin M.; Kuttner, Kenneth N. (American Economic Review, 1992)
Including data from the 1980's sharply weakens the postwar time-series evidence indicating significant relationships between money (however defined) and nominal income or between money and either real income or prices separately. Focusing on data from 1970 onward destroys this evidence altogether. Evidence indicating cointegration of real income and real money balances, with due allowance for the effect of interest rates, also deteriorates when the sample extends through the 1980's. A positive finding is that the spread between the commercial paper rate and the Treasury bill rate consistently contains highly significant information about future movements in real income.